2016
DOI: 10.1007/s00038-016-0789-9
|View full text |Cite
|
Sign up to set email alerts
|

Caste-ethnic disparity in vaccine use among 0- to 5-year-old children in Nepal: a decomposition analysis

Abstract: Nepal's national vaccine programs should increase focus on reaching geographically distant populations, and continue to develop vaccination-related education efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…In Nepal, the majority of research on immunisation has emphasised evaluating factors that affect access to healthcare as well as the quality of service delivery, including the vaccination rates. 6 Previous research in Nepal has found that poverty, geographic location (difficult terrain), being from a low caste or indigenous population, traditional cultural attitudes, being woman and low levels of maternal education all reduce the likelihood that a child will be immunised. 2 6 7 10 Previous research 6 found that children from indigenous and previously untouchable caste (eg, Dalits) were less likely to be immunised than high caste children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nepal, the majority of research on immunisation has emphasised evaluating factors that affect access to healthcare as well as the quality of service delivery, including the vaccination rates. 6 Previous research in Nepal has found that poverty, geographic location (difficult terrain), being from a low caste or indigenous population, traditional cultural attitudes, being woman and low levels of maternal education all reduce the likelihood that a child will be immunised. 2 6 7 10 Previous research 6 found that children from indigenous and previously untouchable caste (eg, Dalits) were less likely to be immunised than high caste children.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous research in Nepal has found that poverty, geographic location (difficult terrain), being from a low caste or indigenous population, traditional cultural attitudes, being woman and low levels of maternal education all reduce the likelihood that a child will be immunised. 2 6 7 10 Previous research 6 found that children from indigenous and previously untouchable caste (eg, Dalits) were less likely to be immunised than high caste children. Terai caste and Muslim children were not included in the study analysis.…”
mentioning
confidence: 99%
“…Negligible or contrasting differences between urban and rural settings were noted in Cambodia, Indonesia, and South Africa with general geographic heterogeneity suggested in Afghanistan, Mozambique, Nepal, and Togo [77, 41, 78, 79, 80, 81, 38, 82, 83, 84, 85, 86, 87, 88, 89]. Dropout of vaccination driven by transport costs and access was highlighted in South Africa and Uganda, despite mitigation through outreach activities [90, 91].…”
Section: Resultsmentioning
confidence: 99%
“…Ethnicity or caste were found to be significant factors contributing to immunisation coverage in Bangladesh, Cambodia, China, Ethiopia, Gambia, India, Namibia, Nepal, Pakistan, and Vietnam with lower immunisation rates among ethnic minorities [71, 41, 97, 56, 51, 100, 93, 82, 99, 86, 85]. In India and Nepal, caste was found to be a highly significant contributor to immunisation coverage, with children from lower castes less likely to be immunised [99, 100, 86, 85]. Though the gap for oral polio vaccine (OPV) coverage in India declined as a result of caste over time, it remained significant at the bivariate level, when results were unadjusted for other potential confounding factors [100].…”
Section: Resultsmentioning
confidence: 99%
“…Ironically, the government's priority for full vaccination has pushed some clients out of the health service delivery chain for two primary reasons. First, various researchers have noted that clients who miss vaccinations are likely to be members of the most vulnerable and marginalized groups [27][28][29]. They face significant distance and travel challenges and often cannot allocate time for travel, mostly because of financial constraints and the need to be continuously engaged in income-generating tasks.…”
Section: Positive Service Biasmentioning
confidence: 99%